Ruthenian Translation of the Czech Book Lucidář (1563) According to the Ukrainian Manuscript Copy of the Mid-Seventeenth Century (prepared by Sergey Temchin) - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2024)
-
Keywords: -